A hydraulic specific energy performance indicator for coiled tube turbodrilling - Mokaramian, A.; Rasouli, Vamegh; Cavanough, G. (ARMA, 2012)
Efficient drilling of hard rocks in mineral exploration requires a comprehensive knowledge of the energy spent at the bit. The use of mechanical specific energy (MSE) proposed in the past for drilling performance studies does not consider the impact of fluid hydraulics and therefore the concept of Drilling Specific Energy (DSE) was later developed to apply the hydraulics parameters into the drilling performance optimization. With respect to the purpose of mineral exploration, coiled tube (CT) Turbodrilling has been proposed recently for deep hard rocks mineral exploration applications, with several advantages over conventional drilling methods. Coiled tube (CT) is a continuous pipe and consequently a downhole motor is needed to provide rotation and mechanical power to the bit. If DSE is to be used as a drilling performance indicator when downhole motors are part of the bottom hole assembly (BHA) it should be modified in such a way that it includes motor specifications in the calculations. In this paper, a methodology is presented for performance optimization in CT Turbodrilling with respect to specific energy performance models. As a result, a hydraulic specific energy performance indicator is defined for CT Turbodrilling in hard rocks mineral exploration.